INTERNALIZING THE VALUE OF RELIGIOUS MODERATION IN SCHOOLS ACCORDING TO AL FARABI'S PHILOSOPHY - Nurcholifah, Anis; Kasianah, Kanti; Simanjuntak, Nensy Megawati; Huda, Nuril (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
In the era of digitalization, everyone can easily access religious issues that occur in society. Understanding Philosophy is expected to be able to minimize problems that arise in society and in the school environment. Religion and philosophy both have an important role in the process of internalizing students' values of religious moderation while at school. Students will be instilled with a true and tolerant understanding of religion. With a correct understanding of religion and philosophy, the school facilitates the process of internalizing moderate religious values in society. It was through Al-Farabi's philosophy that first gave rise to the idea that revelation and philosophy are studies that have the same goal in their substantive form, namely as the first science of truth. Al-Farabi and his leading philosophers explained that the religion brought by a prophet reaches the peak truth through revelation, while a philosopher reaches the peak truth through the power of reason and reflections using ratios. Religion and revelation have an integration point where they complement each other. The internalization of the value of religious moderation in schools must be given from an early age, so that students have the correct knowledge and understanding of moderate and non-radical religions.